Physics teachers’ professional development on measurement uncertainty: A commognitive approach - Ofek Sivan; David Perl-Nussbaum; Edit Yerushalmi (Physical Review Physics Education Research)
In this paper, we demonstrate the fruitfulness of a theoretical framework called Commognition, developed in the context of mathematics education research, for conceptualizing and analyzing a professional development (PD) process on measurement uncertainty for secondary physics teachers. Evaluating measurement uncertainty is an important learning goal in the physics lab and is key to determining the validity of an experiment. While research has mapped difficulties students face and teaching strategies to support them, teacher PD still requires attention, both in capturing teachers’ existing perceptions and in designing PD activities that address these perceptions and support teachers in adopting a more scientifically aligned discourse on measurement uncertainty. Commognition perceives learning as becoming a participant in the discourse of a specific professional community. A discourse consists of keywords, visual mediators, narratives, and routines—and metarules that govern their use. The appropriation of a new discourse involves reconciling conflicts between the metarules of learners’ existing discourse and the new discourse (i.e., commognitive conflicts). We adopted the commognitive framework in all phases of our PD design. First, we mapped the canonical discourse we intended our teachers to adopt versus the prevailing discourse of physics teachers in our national context. Following this mapping, we designed PD tasks intended to lead participants to acknowledge the limitations of their existing discourse on measurement uncertainty as a precursor to internalizing the canonical discourse. Finally, the commognitive framework served as an analytical lens to detect commognitive conflicts involved in collaborative sensemaking among the teachers and between them and the PD facilitators. We demonstrate this type of analysis in a case study, in which learners who hold different discursive metarules encounter implicit commognitive conflicts and discuss implications and untapped opportunities for physics teachers’ PD process on measurement uncertainty.